Night vision exploring the infrared universe - Rowan-Robinson, Michael 1942- (Cambridge Univ. Press, 2013)
"Drawing on exciting discoveries of the last forty years, Night Vision explores how infrared astronomy, an essential tool for modern astrophysics and cosmology, helps astronomers reveal our Universe's most fascinating phenomena - from the birth of stars in dense clouds of gas to black holes and distant colliding galaxies and the traffic of interstellar dust from the formation of our Solar System. While surveying the progress in infrared observation, astronomer Michael Rowan-Robinson introduces readers to the pioneering scientists and engineers who painstakingly developed infrared astronomy over the past two hundred years. Accessible and well illustrated, this comprehensive volume is written for the interested science reader, amateur astronomer or university student, while researchers in astronomy and the history of science will find Rowan-Robinson's detailed notes and references a valuable resource"--